Electrochemical and pitting corrosion resistance of AISI 4145 steel subjected to massive laser shock peening treatment with different coverage layers. (February 2017) - Lu, J.Z.; Han, B.; Cui, C.Y.; Li, C.J.; Luo, K.Y.
Abstract: The effects of massive laser shock peening (LSP) treatment with different coverage layers on residual stress, pitting morphologies in a standard corrosive solution and electrochemical corrosion resistance of AISI 4145 steel were investigated by pitting corrosion test, potentiodynamic polarisation test, and SEM observations. Results showed massive LSP treatment can effectively cause an obvious improvement of pitting corrosion resistance of AISI 4145 steel, and increased coverage layer can also gradually improve its corrosion resistance. Massive LSP treatment with multiple layers was shown to influence pitting corrosion behaviour in a standard corrosive solution. Graphical abstract: Highlights: Laser shock peening causes an increase of pit corrosion resistance of 4145 steel. Corrosion resistance of 4145 steel increases with increasing LSP coverage layer. Corrosion reactions of 4145 steel in both corrosive environments are presented. Mechanism of laser shock peening on corrosion behaviour was also entirely revealed.